Responding to Distress Choosing Between Care and Food: Attachment Orientation and Emotion Regulation - Uccula, Arcangelo; Enna, Mauro; Mulatti, Claudio (Frontiers in Psychology, 2022)
According to attachment theory, care seeking is the primary coping strategy in threatening situations. However, anxious and avoidant individuals often use secondary regulation strategies. The purpose of this study was to test whether, in a potentially threatening situation, the participants’ attachment orientation affects whether they prefer to resort to care or food to regulate their negative emotions. Ninety-two participants took part in an experimental situation in which they had to choose between pictures of care or food, following the presentation of threatening images randomly alternating with neutral ones. Results showed that care pictures were chosen to a greater extent in the threatening condition compared to the food pictures and to the neutral ones, without distinction of attachment orientation. In addition, in the threatening condition anxious individuals chose care less than non-anxious do. Finally, avoidant participants chose care pictures to a lesser extent than individuals low on avoidance in the neutral condition but not in the threatening one. In conclusion, attachment anxiety was associated with more difficulty in the choice of representation of care in a threatening condition, while avoidant individuals show their defensive strategies in the neutral condition rather than in the threatening condition.